(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper proposes a new closed loop control bidirectional buck-boost converter, which is a key component in a photovoltaic and energy storage system (PV-ESS). Conventional bidirectional buck-boost converters for ESSs operate in discontinuous conduction mode (DCM) to achieve zero-voltage-switching turn-on for switches. However, operation in DCM causes high ripples in the output voltage and current, as well as low power-conversion efficiency. To improve on the performance of the conventional converter, the proposed converter has a new combined structure of a cascaded buck-boost converter and an auxiliary capacitor. The combined structure of the proposed converter reduces the output current ripple by providing a current path and the efficiency is increased. The proposed Closed loop control converter has a maximum efficiency of 98%, less than 5.14 Vp.p of output voltage ripple, and less than 7.12 Ap.p of output current ripple. These results were obtained at an input voltage of 160 V, switching frequency of 45 kHz, output voltage of 80 320 V, and output power of 16 160 W. The experimental results show that the proposed converter has improved performance compared to the conventional converter.